Fatores de virulência de Bacillus cereus sensu stricto isolados de alimentos - Luís Renato dos Santos Mascarenhas (2018)
The present study aimed to evaluate the presence of virulence factors in 65 strains of Bacillus cereus sensu stricto (s.s) isolated from food. All 65 strains used in this study were phenotypically characterized for B. cereus s.s. and also genotypically for the determination of the presence of genes encoding virulence factors. The following genes encoding virulence factors were investigated: nheA, nheB, hblA, hblC, hblD,, cytK-1, cytK-2, ces, clo, hlyII, hlyIII, pi-plc, pc-plc and sph. All strains of B. cereus s.s. were positive for the nheA and nheB genes encoding the NHE toxin. The genes encoding the HBL complex (hblA, hbLC and hblD) were detected in 47 (72.3%) samples and in 3 samples, only hblA and hblC gens were detected. The cytK-2 gene was detected in 38 (58.4%) samples. All strains were negative for the ces and cytK-1 genes. The analysis of the occurrence of the genes encoding the enterotoxins allowed the classification of the 65 strains into 5 toxigenic profiles. The predominant toxigenic profile was I, which includes strains positive for all genes minus ces and cytK-1. Concerning the occurrence of the genes encoding the other virulence factors, the genes of clo, hlyIII and hlyII haemolysins were detected in 65 (100%), 44 (67.7%) and 14 (21,5%) of the 65 strains evaluated, respectively. With respect to the occurrence of the three genes encoding the phospholipases pcplc, sph and piplc, their products were amplified in 49 (75.4%), 42 (64.6%) and 42 (64.6%) of the evaluated strains respectively. The analysis of the occurrence of genes coding for hemolysins and phospholipases allowed the classification of the strains into 20 virulence profiles. The predominant virulence profile was II, which includes positive strains for all virulence genes, minus hlyII. The results of the present work suggest that the strains of B. cereus s.s. isolates of food present several virulence factors involved in the pathogenesis of B. cereus s.s infections, representing a potential risk for causing food poisoning and opportunistic infections. Further studies involving cytotoxicity testing and affiliation to phylogenetic groups determined by panC gene sequencing should be performed for a better risk assessment of such lineages.